Ultrasonographic evaluation of canine hepatic disorders - Renjith R (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 2003)
Study on 'Ultrasonographic evaluation of canine hepatic disorders' was conducted on forty eight dogs to evaluate the utility of ultrasonography as a tool for early and better diagnosis of liver diseases and classify liver diseases based on ultrasonographic findings. Parameters studied were history and clinical signs, physical examination, ultrasonography of liver, ultrasound guided biopsy, haematology and serum biochemistry, post-mortem examination and histopathology. Specific clinical signs noticed were ascites and icterus. Physical examination revealed abdominal distension, yellowish discolouration of skin and hepatomegaly. Primary liver disorders identified by ultrasound scans were haematoma, lymphosarcoma, hepatitis due to leptospirosis, cirrhosis, fibrosis, fatty infiltration, chronic active hepatitis, portal hypertension and portosystemic shunt. Secondary changes noticed in liver were due to pyometra, proctitis and cholecystitis, hepatic calcification in chronic renal failure and passive venous congestion in right sided heart failure. Ultrasound guided biopsy confirmed lymphosarcoma, fatty infiltration and , chronic active hepatitis. Histological changes in leptospirosis were chronic venous . and sinusoidal congestion whereas ~n cirrhosis, fibrosis and pseudo lobulation were the prominent histological change. Alkaline phosphatase and Alanine aminotransferase levels were above normal values in all the cases studied. From the present study it was inferred that ultrasonography was a valuable tool for diagnosing hepatopathies along with clinico-pathological and ultrasound guided biopsy.